Identification and alternative management of downy mildew in rose - Álvarez Romero, Pablo Israel; García Velasco, Rómulo; Mora Herrera, Martha Elena; Salgado Siclan, Martha Lidya; Domínguez Serrano, Daniel (Revista Mexicana de Ciencias Agrícolas, 2018)
The downy mildew caused by Peronospora sparsa Berkeley is one of the most important diseases of the rose bush in Mexico, causing 100% losses. Its management is based on fungicides in continuous applications that tend to generate resistant populations. The search for alternatives is indispensable. In the present work, the morphometric and molecular identity of the agent associated with the downy mildew of the rose was confirmed, the effectiveness of the potassium phosphite (K3PO3), chitosan, silicon and mefenoxam was evaluated for the management of the disease and its effect on the length and diameter of floral stem. The study was conducted in summer and fall of 2013 in Tenancingo, State of Mexico. The morphometric characterization was carried out under a compound and scanning electron microscope. For molecular characterization, the ribosomal DNA of the ITS region was amplified with primers PS3 and PS1. The treatments were: potassium phosphite (K3PO3), chitosan, silicon, mefenoxam and control and were applied at weekly intervals. The experimental design was randomized blocks and the mean comparison was by Tukey (α= 0.05). Morphometric and molecular data corresponded to Peronospora sparsa. K3PO3 and silicon reduced the incidence and severity with respect to the control. The treatment with K3PO3 showed increases of 24.8 and 97.5% in the length of stems with diameters of 7.5 and 6.2 mm in summer and autumn respectively, comparing with the control. Thus, K3PO3 and silicon can be alternatives in the management of downy mildew of the rose bush under greenhouse conditions.
Keywords: Peronospora sparsa; potassium phosphite; incidence; severity